Delivery of cardiovascular progenitors with biomimetic microcarriers reduces adverse ventricular remodeling in a rat model of chronic myocardial infarction. (May 2021) - Garbayo, E.; Ruiz-Villalba, A.; Hernandez, S.C.; Saludas, L.; Abizanda, G.; Pelacho, B.; Roncal, C.; Sanchez, B.; Palacios, I.; Prósper, F.; Blanco-Prieto, M.J.
Abstract: Despite tremendous progress in cell-based therapies for heart repair, many challenges still exist. To enhance the therapeutic potential of cell therapy one approach is the combination of cells with biomaterial delivery vehicles. Here, we developed a biomimetic and biodegradable micro-platform based on polymeric microparticles (MPs) capable of maximizing the therapeutic potential of cardiac progenitor cells (CPCs) and explored its efficacy in a rat model of chronic myocardial infarction. The transplantation of CPCs adhered to MPs within the infarcted myocardial microenvironment improved the long-term engraftment of transplanted cells for up to one month. Furthermore, the enhancement of cardiac cellular retention correlated with an increase in functional recovery. In consonance, better tissue remodeling and vasculogenesis were observed in the animals treated with cells attached to MPs, which presented smaller infarct size, thicker right ventricular free wall, fewer deposition of periostin and greater density of vessels than animals treated with CPCs alone. Finally, we were able to show that part of this beneficial effect was mediated by CPC-derived extracellular vesicles (EVs). Taken together, these findings indicate that the biomimetic microcarriers support stem cell survival and increase cardiac function in chronic myocardial infarction through modulation of cardiac remodeling, vasculogenesis and CPCs-EVs mediated therapeutic effects. The biomimetic microcarriers provide a solution for biomaterial-assisted CPC delivery to the heart. Statement of significance: In this study, we evaluate the possibility of using a biomimetic and biodegradable micro-platform to improve cardiovascular progenitor therapy. The strategy reported herein serves as an injectable scaffold for adherent cells due to their excellent injectability through cardiac catheters, capacity for biomimetic three-dimensional stem cell support and controllable biodegradability. In a rat model of chronic myocardial infarction, the biomimetic microcarriers improved cardiac function, reduced chronic cardiac remodeling and increased vasculogenesis through the paracrine signaling of CPCs. We have also shown that extracellular vesicles derived from CPCs cultured on biomimetic substrates display antifibrotic effects, playing an important role in the therapeutic effects of our tissue-engineered approach. Therefore, biomimetic microcarriers represent a promising and effective strategy for biomaterial-assisted CPC delivery to the heart. Graphical abstract: Image, graphical abstract